Real-Time Quantitative Evaluation on the Longitudinal Slip Performance of Spherical Steel Bearings of Long-Span Bridges - Shiyang Xu; Xin Zhou; Gaoxin Wang; Youliang Ding (Advances in Civil Engineering)
Spherical steel bearings play an important role in the normal longitudinal expansion of the main girders of long-span bridges. With the increase in service time, the wear damage will deteriorate the longitudinal slip performance of spherical steel bearings. In this research, a method of real-time quantitative evaluation on longitudinal slip performance is proposed through monitoring data analysis, correlation analysis, damage evaluation analysis, and experiment data analysis. Monitoring data analysis shows that the temperature field has a good linear relationship with longitudinal displacement. Correlation analysis shows that this relationship is well described by a time-varying multiple linear regression model. Furthermore, bearing friction is used as an index for real-time quantitative evaluation, and a large value of bearing friction indicates serious damage. An evaluation model considering the influence of temperature field and bearing frictions is proposed. The time-varying values of bearing frictions are calculated through Kalman filtering analysis. Experimental results show that the maximum evaluation error of this method is less than 5%, verifying that the proposed method is feasible for real-time quantitative evaluation on the longitudinal slip performance of bridge bearings.